Health Communication for Health Promotion in Community - บัญชรหัตถกิจ พรรณี; อัครวีรวัฒน์ ธนปนันท์ (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2022)
At present, in the currents of the world, it has evolved nonstop, even for a fraction of a second, and in terms of dynamic communication. It’s the age of borderless communication. Therefore, health communication is an important and necessary to be a tool to promote the health for the people in the community. For many decades, health communication has been used as a tool to promote health in the community. But it’s still challenging for public health professionals to adopt the principles of communication, to be a mechanism, and to be a mediator for bringing knowledge, health information to the public. Especially, in communities where health communication must take into account the communication patterns in accordance with the context of the community, in accordance with traditions, cultures, beliefs, community lifestyles. The appropriated health communication that is met the people’s requirements, it will be truly accessible health service. As a result, people gain knowledge, understanding that leads to health behavior modification in the long run. All people can be self-reliant on an individual, family, and community levels, and form to be a well-being community by steadily, prosperously and sustainably that will reach the Sustainable Development Goals in the future.